A Classic Herbal Formula Danggui Beimu Kushen Wan for Chronic Prostatitis: From Traditional Knowledge to Scientific Exploration. (13th November 2018) - Li, Hong; Hung, Andrew; Yang, Angela Wei Hong
Abstract : Chronic prostatitis (CP) is a chronic inflammation in the prostate with unsatisfactory management. Danggui Beimu Kushen Wan (DBKW) is a classic formula developed 1800 years ago for patients with difficult urination and it has been widely utilized for CP in modern days. However, scientific understanding of DBKW on CP has not been systematically reviewed. First, we searched the Encyclopedia of Traditional Chinese Medicine for the etiologies and pathogeneses of CP-like symptoms and DBKW and compared their similarities and differences from traditional Chinese medicine and conventional medicine perspectives. Then, we searched 21 electronic databases to identify potential clinical and experimental studies. Characteristics of included studies, ingredients, herb frequency, and possible mechanisms of actions were descriptively summarized. Risk of bias of randomized controlled trials (RCTs) was evaluated using the Cochrane risk of bias assessment tool. A total of 290 studies were identified. Six clinical studies, including four RCTs and two case series, and eight experimental studies were included. Clinical studies indicated that DBKW used alone or as an adjunct therapy significantly reduced the CP symptom scores and decreased the expressed prostatic secretions-pH when compared to antibiotics or α -blocker. Most RCTs have high or unclear risk of bias. Experimental studies revealed that DBKW may have effects on anti-inflammation, antibacteria, antioxidation, sex hormone regulation, and immunoregulation. DBKW demonstrated a great potential in the treatment of CP. High-quality RCTs and network pharmacological studies should be considered for future research.